Socio-cultural proximity, daily life and shopping tourism in the Dutch–German border region - Szytniewski, Bianca; Spierings, Bas; Velde, Martin van der (Tourism Geographies, 2016)
Abstract: „This paper analyses feelings of socio-cultural proximity and distance with a specific focus on the tourist experience in cross-border shopping and everyday life practices in border regions. We examined shopping practices of Dutch border crossers who visit the German town Kleve in the Dutch–German border region. This particular border context has allowed us not only to reflect on a multidimensional approach towards socio-cultural proximity and distance, but also to examine how these different dimensions express themselves in the tourist experience when it comes to people and places that are geographically ‘close’ but assumingly socially and culturally ‘distant’ from home. Although some differences prompted feelings of discomfort, in particular, differences in social engagement, feelings of comfort stand out in our analysis of cross-border shopping tourism. Furthermore, our study shows that shopping tourism and exoticism, on the one hand, and everyday routines and the mundane, on the other hand, are closely intertwined in the lives of people living in a border region, resulting in a fluid interpretation of the exotic and the mundane in the cross-border context.“
Keywords: Einkaufen; Grenzgebiet; Kleve (Kreis Kleve); Mobilität; Sozialraum; Tourismus; Verbrauch

Der Fremdenverkehr im deutsch-niederländischen Grenzgebiet der EUREGIO. Entwicklungsstand und -perspektiven - Otto, Eberhard (Westmünsterland - Ostniederlande. Entwicklung und Stellung eines Grenzraumes. Vorträge auf der Jahrestagung der Geographischen Kommission in Vreden 1983, 1984)
Keywords: EUREGIO (Körperschaft); Grenzüberschreitende Kooperation; Grenzüberschreitende Regionalplanung; Münsterland (West); Niederlande (Ost); Tourismus